(untitled) (Community Based Medical Journal, 2023)
A quasi-experimental study was conducted at Radiation Oncology Department of National Institute of Cancer Research & Hospital (NICRH), Dhaka, Bangladesh, between November 2020 and October 2021, to determine the efficacy of cryotherapy in comparison to standard oral care to prevent oral mucositis in head and neck cancer patients during receiving CCRT. A total 100 Patients (50 patients in each arm) were included in this study according to inclusion and exclusion criteria by purposive sampling technique. All patients in Arm A and Arm B received total 66 Gray in 33 daily fractions, 1 fraction per day, 5 fractions per week and inj. Cisplatin 40mg/m² was given intravenously 2/3 hours before radiotherapy on 1st day and then weekly. Arm A received cryotherapy and Arm B received standard oral care. Intervention started from the 1st day of CCRT up to the end of CCRT. WHO oral mucositis grading and visual analogue scale (VAS) were employed to determine the effects. All the information was recorded in a pre-tested semi-structured questionnaire. Total 100 patients (50 patients in each arm) were enrolled. Mean age of the patients of Arm A and Arm B was 55.28±7.82 and 55.92±8.33 respectively. Male and female ratio was 6.14:1 in two Arms. Other demographic profile, baseline characteristics were statistically not significant in both arms (P>0.05). The grade-3 mucositis appeared after 5th week in Arm B and after 6th week in Arm A. The incidence of grade- 3 mucositis after 5th week during CCRT to 4 weeks after completion of therapy was 6% vs 0%, 14% vs 6%, 22% vs 10%, 14% vs 6%, 8% vs 2%, respectively for arm B and Arm A (P<0.05). Total number of patients suffering from grade 3 mucositis was 6 (12%) and 12 (24%) for Arm A and Arm B respectively (p value was <0.05). The mean duration of grade-3 or more mucositis between Arm A and Arm B was 2.04±1.78 and 10±1.72 days respectively (P<0.05). The difference of median pain intensity between two arms was not statistically significant for 1st and 2nd week (P>0.05). However, it was significant after 3rd week during CCRT to 4 weeks after completion of CCRT (P<0.05). Cryotherapy during CCRT may be beneficial to prevent oral mucositis and pain than maintaining standard oral care. CBMJ 2023 January: vol. 12 no. 01 P: 03-11